2002
DOI: 10.1124/jpet.102.040667
|View full text |Cite
|
Sign up to set email alerts
|

SSR182289A, a Novel, Orally Active Thrombin Inhibitor: In Vitro Profile and ex Vivo Anticoagulant Activity

Abstract: SSR182289A competitively inhibits human thrombin (K i ϭ 0.031 Ϯ 0.002 M) and shows good selectivity with respect to other human proteases, e.g., trypsin (K i ϭ 54 Ϯ 2 M), factor Xa (K i ϭ 167 Ϯ 9 M), and factor VIIa, factor IXa, plasmin, urokinase, tPA, kallikrein, and activated protein C (all K i values Ͼ250 M). In human plasma, SSR182289A demonstrated anticoagulant activity in vitro as measured by standard clotting parameters (EC 100 thrombin time 96 Ϯ 7 nM) and inhibited tissue factor-induced thrombin gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…For example, comparison of the direct thrombin inhibitors SSR182289A and melagatran shows that melagatran possesses higher i.v. antithrombotic potency than SSR182289A but is also a more potent thrombin inhibitor in vitro (Berry et al, 2002), although this factor alone appears not to fully explain the difference in antithrombotic potency. Argatroban, which has a K i value against thrombin (Bush, 1991) similar to that reported for SSR182289A (Berry et al, 2002), shows comparable i.v.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…For example, comparison of the direct thrombin inhibitors SSR182289A and melagatran shows that melagatran possesses higher i.v. antithrombotic potency than SSR182289A but is also a more potent thrombin inhibitor in vitro (Berry et al, 2002), although this factor alone appears not to fully explain the difference in antithrombotic potency. Argatroban, which has a K i value against thrombin (Bush, 1991) similar to that reported for SSR182289A (Berry et al, 2002), shows comparable i.v.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously shown that i.v. or oral administration of SSR182289A produces dose-related increases in coagulation parameters (thrombin time, ecarin clotting time, and activated partial thromboplastin time) in several animal species (rat, rabbit, dog, and macaque) (Berry et al, 2002). In this context, the ecarin clotting time has been reported to be a good predictor of antithrombotic effects for direct thrombin inhibitors in rat venous and arterial thrombosis models (Berry et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations